A Niche Analysis of Three Interpersonal Communication Technologies: Examining the Competition among Facebook, Line, and Email - Shu-Chu Li; Yen-Shen Chen; Linlin Ku (International Telecommunications Society (ITS), 2017)
Adopting Dimmick's niche theory as its theoretical framework, this study examined the gratifications obtained and gratification opportunities from Facebook, Line, and email to understand the competitive relationships among the three interpersonal media in Taiwan. This study first conducted twenty intensive interviews to construct questionnaire items to measure users' gratifications obtained and gratification opportunities from the three media. Then, a telephone survey was conducted to collect data and 1042 valid calls were obtained. The data analysis shows that (1) among the three interpersonal media, Line had the widest niche breadth and the highest scores of competitive superiority and competed strongly with Facebook; and (2) the competitive superiority scores of a medium were a powerful predictor of the use history of that medium.
Keywords: 330; the theory of the niche; Facebook; Line; email; gratifications obtained; gratification opportunities